2003
DOI: 10.1046/j.1440-1746.2003.02932.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of Japanese reflux esophagitis patients as determined by Los Angeles classification

Abstract: We observed that age, hiatal hernia and a lower rate of gastric mucosal atrophy were associated with the proportion of mucosal breaks accompanying esophagitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
76
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 18 publications
(29 reference statements)
5
76
0
Order By: Relevance
“…Today, the incidence of RE is reported to be 10%-20% in Europe and the United States [23][24][25] , and 14%-16% in Japan [26][27][28] . While the incidence of RE in Japan is considered low as compared to Europe and the United States, the incidence of RE in Japan has increased due to the westernization of the Japanese diet, the rapidly growing elderly population, and lower H pylori infection rates [26][27][28] . Parkman [5] has reported that the incidence of RE in patients was 20% (4/20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Today, the incidence of RE is reported to be 10%-20% in Europe and the United States [23][24][25] , and 14%-16% in Japan [26][27][28] . While the incidence of RE in Japan is considered low as compared to Europe and the United States, the incidence of RE in Japan has increased due to the westernization of the Japanese diet, the rapidly growing elderly population, and lower H pylori infection rates [26][27][28] . Parkman [5] has reported that the incidence of RE in patients was 20% (4/20).…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, with respect to the severity of RE, most patients are reported to have mild esophagitis (Grade A or B under the Los Angeles classification [26,27] . In the present study, all patients had mild esophagitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastroesophageal reflux disease (GERD) is a common disease in Western countries [1][2][3], and the number of patients with GERD is increasing in Japan [4][5][6][7]. Gastric acid has an important role in the pathogenesis of GERD.…”
Section: Introductionmentioning
confidence: 99%
“…Male sex, old age (>65 years old), hiatal hernia, smoking, alcohol, Caucasian race, and obesity are independent risk factors associated with asymptomatic esophagitis (8,(15)(16)(17). Atrophy, Helicobacter pylori infection, and peptic ulcer are not considered to be risk factors for provoking asymptomatic EE, while there are varying reports of association between BMI and asymptomatic EE (7,8,18).…”
Section: Discussionmentioning
confidence: 99%